2023
DOI: 10.1002/advs.202306711
|View full text |Cite
|
Sign up to set email alerts
|

Fast Energy Storage of SnS2 Anode Nanoconfined in Hollow Porous Carbon Nanofibers for Lithium‐Ion Batteries

Fanghua Liang,
Huilong Dong,
Jiamu Dai
et al.

Abstract: The development of conversion‐typed anodes with ultrafast charging and large energy storage is quite challenging due to the sluggish ions/electrons transfer kinetics in bulk materials and fracture of the active materials. Herein, the design of porous carbon nanofibers/SnS2 composite (SnS2@N‐HPCNFs) for high‐rate energy storage, where the ultrathin SnS2 nanosheets are nanoconfined in N‐doped carbon nanofibers with tunable void spaces, is reported. The highly interconnected carbon nanofibers in three‐dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 89 publications
0
3
0
Order By: Relevance
“…During the initial charging scan, the peak at 0.2 V is attributed to the release of Li + ions from carbon, while the anodic peak at 1.1 V signifies the extraction of Li + ions from the SEI film. From the second scan onward, there is no significant alteration in the area under the curve, indicating that the SEI layer is established during the first cycle, and the microstructure remains unchanged. , …”
Section: Resultsmentioning
confidence: 94%
“…During the initial charging scan, the peak at 0.2 V is attributed to the release of Li + ions from carbon, while the anodic peak at 1.1 V signifies the extraction of Li + ions from the SEI film. From the second scan onward, there is no significant alteration in the area under the curve, indicating that the SEI layer is established during the first cycle, and the microstructure remains unchanged. , …”
Section: Resultsmentioning
confidence: 94%
“…7b shows the HER and OER LSV curves of LSC/MoS 2 in 1 M KOH electrolyte. 56–59 It can be found that the HER and OER overpotentials of LSC/MoS 2 are 470 and 346 mV, respectively at 100 mA cm −2 . In order to achieve the current density of 10 mA cm −2 , LSC/MoS 2 ‖LSC/MoS 2 requires a corresponding voltage of 1.48 V, which is lower than that of Pt/C‖RuO 2 (1.58 V) in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23-0677). 38,39 Besides, no other extra diffraction peaks can be observed, showcasing a high purity of the MSS@NSC and the amorphous nature of the NSC. The surface textures and pore characteristics for the MSS@NSC and MSS are studied through the N 2 sorption measurements.…”
Section: ■ Results and Discussionmentioning
confidence: 99%